High-performance, nickel-containing connector alloys - Emley, Frank (Nickel Development Institute, 1991)
This book describes of High-performance, nickel-containing, connector alloys. Connectors and interconnections are the necessary links tying together and rerouting electrical and electronic power, control, and signal movements between components and operational units in today's high-technology world of computers, communications, automobiles, aircraft, appliances and military and industrial equipment.
Keywords: Nickel alloys.; elektronické knihy; electronic books